An Episode of Pseudothrombocytopenia during Pembrolizumab Therapy in NSCLC Patient - Kinga Krukowska; Robert Kieszko; Katarzyna Kurek; Izabela Chmielewska; Paweł Krawczyk; Janusz Milanowski (Case Reports in Oncological Medicine)
Immunotherapy with immune checkpoint inhibitors (ICI) is a new option of treatment in a growing range of neoplasms. In addition to an antitumor effect, ICI are associated with autoimmune reactions resulting in a wide spectrum of toxicities that have not been seen in patients receiving chemotherapy. In this article, we present a case of a patient with advanced lung adenocarcinoma who developed an EDTA-dependent pseudothrombocytopenia (PTCP) during pembrolizumab therapy. To the best of our knowledge, this is the first reported case of EDTA-dependent PTCP occurring during immunotherapy treatment of nonsmall lung cell cancer with ICI. The phenomenon of EDTA-dependent PTCP may prompt clinical decisions, as unnecessary transfusions or even exclusion from pembrolizumab therapy. Therefore, it is important to be aware of PTCP as a possible side effect of this therapy.